A Brief Description on Reproductive Biology of The Near Threatened Ornamental Fish Ctenops Nobilis Mcclelland, 1845 - S. Bhattacharya; B. K. Mahapatra; J. Maity (Journal of Indian Fisheries Association, 2020)
Due to over-exploitation and decline in population in natural habits, Ctenops nobilis Mcclelland, 1845 has been categorised as near threatened species. For establishing successful breeding and culture protocol of the species under captivity, a detailed information on reproductive biology is utmost important. Keeping view on this, the present research was planned to study important aspects of reproductive biology of the species. The breeding season of the fish extend from late July to September. The males are clearly identified by their broad spouts. It is noted that 50% of females attained first maturity (M50) at 75-85 mm length and 5.50-6.45g weight, whereas male attained maturity at 68-72mm length and 4.75-5.82g weight. The value of GSI ranged between 1.93 and 5.95, while fecundity ranged between 350 and 750 eggs. The finding of present study will be useful in planning captive breeding of the species.